The Effects of Mathematics Activities Based on Community Based Learning to Enhance Mathematical Literacy and Awareness in SDGs for Upper Primary School Students - Jantap, Nattaya; Mahavijit, Pongsatorn; Koolsriroj, Udomluk (Ratchaphruek Journal, 2024)
The objectives of the research were to: 1) Design mathematics activities based on community-based learning; 2) Study the results of using mathematics activities based on community-based learning towards mathematics literacy; and 3) Study the results of using mathematics activities based on community-based learning for upper primary school students towards awareness in SDGS. The research instruments were) five lesson plans, a mathematics literacy test, and the SDGS awareness test. The target group in this study was 39 students in the upper primary level of Banhuatanon School in Mueang District, Chumphon Province, in the second semester of the academic year 2023. Activities are organized based on the mathematics activity plan in the Moderate Class, More Knowledge. Methods used to analyze the data were percentage, mean and standard deviation. The finding showed that 1) the result of using mathematics activities based on community-based learning for upper primary school students towards mathematics literacy, the suitability evaluation results in the most appropriate criteria. 2) The result of the assessment of mathematics literacy for upper primary school students in the target group was an average of 14.73, accounting for 61.38 percent; and 3) The result of the assessment of awareness in SDGS was an average of 3.30, which means that the students had a moderate level of awareness.